Nurses' perceptions of difficult patients - Janetta H Roos (AOSIS, 2005)
The purpose of this article was to explain and describe how professional nurses in the health services experience difficult patients. Opsomming Die doel van hierdie artikel was om te verduidelik en te beskryf hoe professionele verpleegkundiges in gesondheidsdienste moeilike pasiënte ervaar. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.